Pandemic or Not, Worker Subjective Wellbeing Pivots About the Living Wage Point: A Replication, Extension, and Policy Challenge in Aotearoa New Zealand - Carr, Stuart C.; Haar, Jarrod; Hodgetts, Darrin; Jones, Harvey; Arrowsmith, James; Parker, Jane; Young-Hauser, Amanda; Alefaio, Siautu (Frontiers in Psychology, 2022)
Recent pre-pandemic research suggests that living wages can be pivotal for enhancing employee attitudes, job satisfaction, and wellbeing. This article explores whether or not the present COVID-19 pandemic is impacting pivotal links between living wages and employee attitudes and wellbeing, with replication indicating robustness. Twin cohorts of low-waged workers in New Zealand (NZ), one pre- (2018) and one present-pandemic (2020) measured hourly wage, job attitudes and wellbeing as linked to changes in the world of work associated with the pandemic (e.g., job security, stress, anxiety, depression, holistic wellbeing). Job attitudes and wellbeing scores tended to pivot upwards at the living wage level in NZ. These findings replicate earlier findings and extend these into considering wellbeing in the context of a crisis for employee livelihoods and lives more generally. Convergence across multiple measures, constructs, and contexts, suggests the positive impacts of living wages are durable. We draw on Big Push theory to argue that the present government policy of raising legal minimum wages (as NZ has done) may not protect wellbeing until wages cross the living wage Rubicon. Future research should address this challenge.